2020
DOI: 10.37358/rc.20.5.8155
|View full text |Cite
|
Sign up to set email alerts
|

Hot Water Extraction of Crude Polysaccharide from Codonopsis pilosula and Determination of the Rheological Properties

Abstract: The extraction condition of crude polysaccharides from Codonopsis pilosula by hot water reflux method was studied and the results analyzed by kinetic model. Then, the extraction rate and maximum extraction temperature were determined. furthermore, the thermal and pH stability and the rheological properties of the crude polysaccharide were also studied. crude Codonopsis pilosula polysaccharide (CCPP) under different conditions was extracted by hot water reflux method, the content was determined by phenol-sulfur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(29 reference statements)
1
2
0
Order By: Relevance
“…The studies illustrated that highly diverse cropping systems were less affected by soil-borne pathogens than the plant mono-fields or low-diversity fields. This is consistent with the results of crop diseases (Figure 3), and highlighted that FC system not only increased soil bacterial relative abundance but also decreased soil borne pathogens [25][26][27][28].…”
Section: 11benefit Of Plants As Results Of Changes In Soil Microbiasupporting
confidence: 91%
See 1 more Smart Citation
“…The studies illustrated that highly diverse cropping systems were less affected by soil-borne pathogens than the plant mono-fields or low-diversity fields. This is consistent with the results of crop diseases (Figure 3), and highlighted that FC system not only increased soil bacterial relative abundance but also decreased soil borne pathogens [25][26][27][28].…”
Section: 11benefit Of Plants As Results Of Changes In Soil Microbiasupporting
confidence: 91%
“…The mechanisms of replant problem are very complex, and have been considered as including multiple cultural practices, soil conditions and other environmental factors. Previous studies have found the link of long-term continuous cropping systems to many agricultural traits [27]. Leaf area used to measure plant photosynthesis, which was a key factor for agronomic traits.…”
Section: 7the Increased Productivity and Agronomic Traits Under Crmentioning
confidence: 99%
“…However, glutathione status is involved in H2O2-triggered signal transduction, which would influence H2O2 concentration through its antioxidative function [31]. Accordingly, it is still ambiguous whether changes in glutathione status are themselves sensed or rather affect antioxidant enzymes through secondary effects on ROS availability [32][33][34][35][36].…”
Section: Effects Of Melatonin Pretreatment On Non-protein Thiol Contementioning
confidence: 99%